LEADERSHIP COMMUNICATION EDITORIAL IMPROVING THE PERFORMANCE OF JOURNALIST IN THE GENERAL DIRECTION DAILY NEWSPAPERS RIAU - Mashita, Dayang; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Leadership communication is the process of delivering the mind or feelings of a leader to subordinates by using the symbol - a symbol that is meaningful to both parties, in certain situations using a particular medium of communication to change attitudes or behavior of a number of people so that there are certain effects are expected. The purpose of the study was to determine the communication model editors, editorial director of communication and communication climate chief editors in improving the performance of journalists in the General Direction Daily Newspapers Riau.This study used a qualitative method that seeks to provide an overview of the events that have happened and interview techniques through a conversation with a specific intent by both sides, which gives interviewer and interviewee questions to answer. The validity of the data using triangulation technique that compares the data with the results of observation research documentation.From the results of this study found that communication editors in improving the performance of reporters needed communication up and down communication, there is also a form of communication climate chief editor and editorial director of communication in improving the performance of journalists in Daily Newspapers Public Policy, Riau if all such communications running smoothly performance of journalists in the General Direction Daily Newspapers Riau will be maximal.Keywords : Leadership Communication, Performance Of journalist, Newspapers